Bullying in Medical Education: Causes and Its Impact on Student Performance - Ahmed, Touheed (Jurnal Ilmiah WUNY, 2025)
Bullying in medical education is an aggressive behavior that is repeated with the intention of harming the physical, mental, or emotional well-being of individuals perceived as weaker. This behavior often occurs between educators, residents, nurses, and students in medical settings. It violates ethical standards of the medical profession and human rights while negatively impacting the quality of education and healthcare services. This study employs a literature review methodology to analyze the causes and effects of bullying on the performance of medical students. The findings indicate that factors such as hierarchical seniority, insufficient supervision, and academic pressure contribute to bullying, which adversely affects students' mental health and academic performance. Comprehensive preventive measures are required to create a safer learning environment that supports students' well-being.